Impact of occupational noise exposure on the health of educational center workers: A metaanalysis. - Rodriguez-Salazar, Maria; Ortega-Clavijo, Maria; Moreira macias, Eugenia; Chang Camacho, Lidia (EASI: Engineering and Applied Sciences in Industry, 2023)
The World Health Organization settled in 65dB the maximum exposure noise level during the daytime workforce. The effects of occupational exposure to noise extend beyond mere hearing impairment, gathering everything from general discomfort to physiological alterations in human body. A metaanalysis of available literature conducted to examinate the impact of ergonomic noise on the health of workers in educational centers. The systematic review followed the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta Analyses). The analysis of the final sample reveals health effects in 82%, ranging from moderate-level symptoms to potentially dangerous outcomes. The findings revealed a relationship between noise exposure and body effects: voice, hearing and, physiological and psychological aspects. However, the information available is limited to classify these conditions as occupational diseases.
Keywords: noisy classrooms; noise pollution; teachers; hearing health; effects of noise